Diversity of Middle East respiratory syndrome coronaviruses in 109 dromedary camels based on full-genome sequencing, Abu Dhabi, United Arab Emirates - Mohammed Farouk Yusof; Krista Queen; Yassir Mohammed Eltahir; Clinton R Paden; Zulaikha Mohamed Abdel Hameed Al Hammadi; Ying Tao; Yan Li; Abdelmalik Ibrahim Khalafalla; Mang Shi; Jing Zhang; Muzammil Sayed Ahmed Elhaj Mohamed; Mahmud Hamed Abd Elaal Ahmed; et al. (Emerging Microbes and Infections, 2017)
Middle East respiratory syndrome coronavirus (MERS-CoV) was identified on the Arabian Peninsula in 2012 and is still causing cases and outbreaks in the Middle East. When MERS-CoV was first identified, the closest related virus was in bats; however, it has since been recognized that dromedary camels serve as a virus reservoir and potential source for human infections. A total of 376 camels were screened for MERS-Cov at a live animal market in the Eastern Region of the Emirate of Abu Dhabi, UAE. In all, 109 MERS-CoV-positive camels were detected in week 1, and a subset of positive camels were sampled again weeks 3 through 6. A total of 126 full and 3 nearly full genomes were obtained from 139 samples. Spike gene sequences were obtained from 5 of the 10 remaining samples. The camel MERS-CoV genomes from this study represent 3 known and 2 potentially new lineages within clade B. Within lineages, diversity of camel and human MERS-CoV sequences are intermixed. We identified sequences from market camels nearly identical to the previously reported 2015 German case who visited the market during his incubation period. We described 10 recombination events in the camel samples. The most frequent recombination breakpoint was the junctions between ORF1b and S. Evidence suggests MERS-CoV infection in humans results from continued introductions of distinct MERS-CoV lineages from camels. This hypothesis is supported by the camel MERS-CoV genomes sequenced in this study. Our study expands the known repertoire of camel MERS-CoVs circulating on the Arabian Peninsula.Emerging Microbes & Infections (2017) 6, e101; doi:10.1038/emi.2017.89; published online 8 November 2017